Influence of Certain Physical and Chemical Factors of Cryopreservation on Bone Marrow Cells with Various Initial Structural and Functional Status - Kozlova, Yu. A.; Goltsev, A. N.; Ostankov, M. V. (Problems of Cryobiology and Cryomedicine, 2003)
The structural and functional organisation of bone marrow (BM) cells of the intact rats and with the experimental allergic encephalomyelitis (EAE) after the influence of physical and chemical factors, realised in the process of cryopreservation (pH and osmolarity) was estimated. The data obtained orientate to the possibility for modifying (optimising) the equilibration conditions of donor’s BM with the mentioned pathology at the stage of its preliminary preparing for freezing.